Autophagy as a Cellular Stress Response Mechanism in the Nervous System. Issue 8 (3rd April 2020) - Peker, Nesibe; Gozuacik, Devrim
Abstract: Cells of an organism face with various types of insults during their lifetime. Exposure to toxins, metabolic problems, ischaemia/reperfusion, physical trauma, genetic diseases, neurodegenerative diseases are among the conditions that trigger cellular stress responses. In this context, autophagy is one of the mechanisms that supports cell survival under stressful conditions. Autophagic vesicle engulfs the cargo and transports it to lysosome for degradation and turnover. As such, autophagy eliminates abnormal proteins, clears damaged organelles, limits oxidative stress and helps to improve metabolic balance. Nervous system cells and particularly postmitotic neurons are highly sensitive to a spectrum of insults, and autophagy emerges as one of the key stress response mechanism, ensuring health and survival of these vulnerable cell types. In this review, we will overview mechanisms through which cells cope with stress, and how these stress responses regulate autophagy, with a special focus on the nervous system. Graphical abstract: Image 1 Highlights: Stress factors activate cellular stress response mechanisms in cells. Postmitotic cells in the nervous system are sensitive to cellular stress. Autophagy is a main stress response mechanism in nervous system cells. Autophagy clears damaged proteins and organelles, and maintains metabolic balance. Therapeutic strategies targeting autophagy may alleviate neurodegenerative diseases.